Protozoan co-infections and parasite influence on the efficacy of vaccines against bacterial and viral pathogens - Akoolo, Lavoisier; Rocha, Sandra C.; Parveen, Nikhat (Frontiers in Microbiology, 2022)
A wide range of protozoan pathogens either transmitted by vectors (Plasmodium, Babesia, Leishmania and Trypanosoma), by contaminated food or water (Entamoeba and Giardia), or by sexual contact (Trichomonas) invade various organs in the body and cause prominent human diseases, such as malaria, babesiosis, leishmaniasis, trypanosomiasis, diarrhea and trichomoniasis. Humans are frequently exposed to multiple pathogens simultaneously, or sequentially in the high‐incidence regions to result in co-infections. Consequently, synergistic or antagonistic pathogenic effects could occur between microbes that also influences overall host responses and severity of diseases. The co-infecting organisms can also follow independent trajectory. In either case, co-infections change host and pathogen metabolic microenvironments, compromise the host immune status, and affect microbial pathogenicity to influence tissue colonization. Immunomodulation by protozoa often adversely affects cellular and humoral immune responses against co-infecting bacterial pathogens and promotes bacterial persistence, and result in more severe disease symptoms. Although co-infections by protozoa and viruses also occur in humans, extensive studies are not yet conducted probably because of limited animal model systems available that can be used for both groups of pathogens. Immunosuppressive effects of protozoan infections can also attenuate vaccines efficacy, weaken immunological memory development, and thus attenuate protection against co-infecting pathogens. Due to increasing occurrence of parasitic infections, roles of acute to chronic protozoan infection on immunological changes need extensive investigations to improve understanding of the mechanistic details of specific immune responses alteration. In fact, this phenomenon should be seriously considered as one cause of breakthrough infections after vaccination against both bacterial and viral pathogens, and for the emergence of drug-resistant bacterial strains. Such studies would facilitate development and implementation of effective vaccination and treatment regimens to prevent or significantly reduce breakthrough infections.